Synthesis & Characterization Of “Plum Pudding” Poly (Oligoethylene Glycol Methyl Methacrylate) Hydrogels Using Starch Nanoparticles - Affar, Ali (My University, 2019)
Hydrogels are defined as swellable polymer networks with the mechanical, interfacial, and physical properties similar to native tissues in the body. Nanocomposite hydrogels, defined as hydrogels that either entirely consist of or have embedded nanoparticle phases, have been shown to further expand the range of properties achievable with hydrogels and be suitable in many applications such as building tissue scaffolds. In particular, nanocomposite phases that can be eroded offer interesting potential to construct nanoscale voids that can be made in the gel that may be highly beneficial for applications in drug delivery, bioseparations, and tissue engineering. In this thesis, two methods of incorporating starch nanoparticles (SNPs) into a ultraviolet (UV)-cured poly(ethylene glycol methacrylate) (POEGMA) matrix are described. In the first method, the SNPs were physically entrapped during the curing of the gels. An investigation of the effect of fabrication parameters such as monomer ratios, crosslinker amounts, and entrapped SNP concentration on swelling and shear storage modulus (G’) was performed. Enzymatic degradation of the nanophase was also observed to be possible upon amylase treatment, and the resulting internal morphology was confirmed to have increased internal porosity based on a methylene blue uptake experiment. In the second method, chemically functionalized SNPs were used as the exclusive crosslinker to create the POEGMA network. The swelling and mechanical performance of the SNP-crosslinked hydrogels were investigated and compared to the entrapped SNP gels. A preliminary study of the consequences of degradation of a naturally occurring crosslinker to the enzyme α-amylase was also performed. The combination of cytocompatible components and potential for internal porosity control make gels an interesting platform for tissue scaffolding and bioseparation applications.
Keywords: Hydrogels, composites, starch, nanoparticles, tissue engineering, drug delivery